Grass-roots junior doctor communication network in response to the COVID-19 pandemic: a service evaluation. Issue 2 (3rd May 2021) - Sivananthan, Arun; Machin, Matthew; Zijlstra, Geiske; Harris, Alexander; Radhakrishnan, Shiva T; Crook, Peter; Phillips, Georgina; Denning, Max Christopher; Patel, Nisha; Russell, Georgina; Darzi, Ara; Kinross, James; et al.
Abstract : Background: COVID-19 was declared a worldwide pandemic on 11 March 2020. Imperial College Healthcare NHS Trust provides 1412 inpatient beds staffed by 1200 junior doctors and faced a large burden of COVID-19 admissions. Local problem: A survey of doctors revealed only 20% felt confident that they would know to whom they could raise concerns and that most were getting information from a combination of informal work discussions, trust emails, social media and medical literature. Methods: This quality improvement project was undertaken aligning with Standards for Quality Improvement Reporting Excellence 2.0 guidelines. Through an iterative process, a digital network (Imperial Covid cOmmunications Network; ICON) using existing smartphone technologies was developed. Concerns were collated from the junior body and conveyed to the leadership team (vertical—bottom-up using Google Form) and responses were conveyed from leadership to the junior body (vertical—top-down using WhatsApp and Zoom). Quantitative analysis on engagement with the network (members of the group and number of issues raised) and qualitative assessment (thematic analysis on issues) were undertaken. Results: Membership of the ICON WhatsApp group peaked at 780 on 17 May 2020. 197 concerns were recorded via the Google Form system between 20 March and 14 June 2020. There were five overarching themes: organisational and logistics; clinical strategy concerns; staff safety and well-being; clinical (COVID-19) and patient care; and facilities. 94.4% of members agreed ICON was helpful in receiving updates and 88.9% agreed ICON improved collaboration. Conclusions: This work demonstrates that a coordinated network using existing smartphone technologies and a novel communications structure can improve collaboration between senior leadership and junior doctors. Such a network could play an important role during times of pressure in a healthcare system.